Self-organization in a distributed manufacturing system based on constraint logic programming - Sluga, A.; Butala, P.; Peklenik, J. (CIRP annals, 2001)
The paper addresses the problem of self-organization of manufacturing systems. The objective is to overcome the rigidity of conventional hierarchical structures and to introduce structures that are able to adapt to a dynamic environment. The presented approach is based on the concept of Complex Adaptive Manufacturing Systems. It is characterized by a decomposition of manufacturing objectives and allocation of tasks to work systems as autonomous building blocks in a dynamic environment. The allocation is based on a market mechanism that enables self-organization and optimization of a manufacturing system by evaluation and selection among competing work systems. The approach is implemented in the Constraint Logic Programming environment Eclipse and validated in a simulation experiment.